2004
DOI: 10.2337/diabetes.53.12.3107
|View full text |Cite
|
Sign up to set email alerts
|

Islet Graft Assessment in the Edmonton Protocol

Abstract: The success of the Edmonton Protocol for islet transplantation has provided new hope in the treatment of type 1 diabetes. This study reports on the assessment of 83 human islet grafts transplanted using the Edmonton Protocol since 1999. Cellular composition, as assessed by immunohistochemistry, showed a lower islet purity (ϳ40%) than has been reported in previous studies using dithizone staining to quantitate islet equivalents. Furthermore, grafts were found to contain substantial populations of exocrine and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
147
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(160 citation statements)
references
References 36 publications
(43 reference statements)
12
147
1
Order By: Relevance
“…The results of recent clinical trials in islet transplantation suggest that improved graft survival correlates, to an extent, with the presence of unprocessed exocrine material inadvertently co-transplanted with human islet cells [22]. This material may provide a pool of progenitor cells with the capacity to differentiate to insulin-secreting cells and thus increase the functional beta cell mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of recent clinical trials in islet transplantation suggest that improved graft survival correlates, to an extent, with the presence of unprocessed exocrine material inadvertently co-transplanted with human islet cells [22]. This material may provide a pool of progenitor cells with the capacity to differentiate to insulin-secreting cells and thus increase the functional beta cell mass.…”
Section: Discussionmentioning
confidence: 99%
“…In the present investigation we sought to determine whether appropriate glucose signalling and insulin secretion could be restored in culture by re-establishing cellular interactions between islets and non-endocrine components of the human pancreas. Specifically, we aimed to re-introduce the influences exerted by pancreatic ductal epithelial cells (DECs), which are considered to be a potential source of trophic factors [19], ECM components [20] and beta cell progenitors [21] thought to contribute to sustained graft survival following islet transplantation [22].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that islet recipients who receive greater numbers of ductal cells within islet grafts have better graft function at 2 years post transplant as measured by acute insulin response to glucose [19]. Since ductal progenitors within the grafts may contribute to long-term graft function, it is important to determine the effect of immunosuppressive agents on these cells.…”
mentioning
confidence: 99%
“…Since ductal progenitors within the grafts may contribute to long-term graft function, it is important to determine the effect of immunosuppressive agents on these cells. Indeed, long-term immunosuppression may reduce graft function either by direct drug effects on the beta cells themselves or by effects on ductal cell progenitors that are transplanted with the islets (ductal cells form 20-30% of islet grafts) [19].…”
mentioning
confidence: 99%
“…However, islets in this work were healthy, with a SI between 2 and 20 (Carter et al 2009) not showing any harmful effect of Histopaque on the islets, as supported also by more recent studies performed with Ficoll-based gradients (McCall et al 2011;Mita et al 2010;Lamb et al 2011), nor were any statistical differences between methods observed. However, although GSIS is an important predictor of islet function it does not have a correlation with clinical transplantation outcomes (Ricordi et al 2001;Street et al 2004). Therefore, islets obtained by filtration (with the lowest GSIS and the highest viability) may recover once transplanted and improve their functionality in vivo (Papas et al 2009).…”
Section: Discussionmentioning
confidence: 99%